2021
DOI: 10.1016/j.neo.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation sources coagulation protease cascade and hepatocyte growth factor to support physiological growth and malignant transformation

Abstract: Highlights Ovulatory follicular fluid exerts a long-lasting transformation activity covering throughout the ovulation cycle. The ovulation injury-coagulation proteases-hepatocyte growth factor (HGF) cascade is responsible for the sustained activity. Ovulation sources HGF into the peritoneal cavity, then into the blood circulation. This coagulation-HGF cascade promotes the transformation of fallopian tube epithelial cells and ovarian canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Similar to the endometriotic lesions, the fimbriae, which pick up oocytes, are exposed to the ovulatory follicular fluid (FF) during and after ovulation. The FF carries growth factors, such as IGF2 and hepatocyte growth factor (HGF), to ensure the regeneration of damaged fimbrial and ovarian epithelia after ovulation, as well as the malignant transformation [ 21 , 34 , 35 , 36 ]. Ovulation sources the follicular ingredients into the peritoneal fluid and constitutes the main contents of the peritoneal fluid, which is regarded as an ovarian exudate [ 37 , 38 ].…”
Section: Missing Link 1: Ovulation Is An Overlooked Etiological Facto...mentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the endometriotic lesions, the fimbriae, which pick up oocytes, are exposed to the ovulatory follicular fluid (FF) during and after ovulation. The FF carries growth factors, such as IGF2 and hepatocyte growth factor (HGF), to ensure the regeneration of damaged fimbrial and ovarian epithelia after ovulation, as well as the malignant transformation [ 21 , 34 , 35 , 36 ]. Ovulation sources the follicular ingredients into the peritoneal fluid and constitutes the main contents of the peritoneal fluid, which is regarded as an ovarian exudate [ 37 , 38 ].…”
Section: Missing Link 1: Ovulation Is An Overlooked Etiological Facto...mentioning
confidence: 99%
“…The FF has a high reserve of these coagulation cascade proteins and HGFA/HGF. The cascade is slowly and continuously activated by a tissue factor released in the FF and peritoneal fluid [ 36 ]. Thus, c-MET-expressing tissues, including the FTE and the endometriosis lesions, all receive the signal and may exhibit growth and invasion phenotypes [ 44 ].…”
Section: Missing Link 1: Ovulation Is An Overlooked Etiological Facto...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of the ovulation-induced FTE transformation are becoming increasingly clear. Ovulatory follicular fluid (FF) contains high levels of various carcinogens, such as reactive oxygen species (ROS), insulin-like growth factor (IGF) axis proteins, and coagulation factor-hepatocyte growth factor (HGF) activation cascade proteinases, which confer a range of cell transformation phenotypes, including DNA double-strand breaks [ 8 , 9 ], stemness activation, clonal expansion [ 10 ], anchorage-independent growth, and xenograft tumorigenesis [ 10 , 11 ]. The transformation effect of ovulatory FF is not limited to the FTE transformation.…”
Section: Introductionmentioning
confidence: 99%
“…In all the previous studies, the pro-metastasis activities of ovulation were demonstrated by human FF exposure in vitro or ex vivo [ 8 , 10 , 11 ] or by co-injection of FF, transforming human FTE cells into the peritoneal cavity of immune-compromised mice [ 9 , 12 ]. An in vivo demonstration of the effect of ovulation on HGSC development is lacking.…”
Section: Introductionmentioning
confidence: 99%